Pengaruh Functional Value, Social Value dan Emotional Value terhadap Green Purchase Intention, Dengan Green Trust Sebagai Variabel Intervening (Studi pada Konsumen Produk Ramah Lingkungan di Yogyakarta) - Regi Tuska; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to identify the impact of the variables functional value, social value, and emotional value on the variable green purchase intention with the intervening variable green trust. Quantitative research method was used in this study with data obtained through a questionnaire (gform). Purposive sampling using the Hair formula was used to select a sample of 126 participants who filled out the questionnaire and processed using SPSS 24.0 for analysis using multiple linear regression analysis. This study yielded various results, including a significant positive relationship between the functional value variable and the green trust variable. There is a significant positive relationship between the social value variable and the green trust variable. The emotional value variable does not have a significant influence on the green trust variable. The green trust variable has a significant positive influence on the green purchase intention variable. Functional value does not have a positive and significant effect on green purchase intention. Social value does not have a positive and significant effect on green purchase intention. Emotional value does not have a positive and significant effect on green purchase intention.